Investigation of Structural Properties and Martensitic Phase Transformations in Heat-treated Ni-25.5 at. %Ta High Temperature Shape Memory Alloys - Yildiz, Koksal (Adiyaman University, 2020)
The effect of heat treatment performed at 800 °C, 900 °C and 1000 °C for 1 hour on structural and martensitic transformation properties of Ni-25.5 at.%Ta high temperature shape memory alloy has been examined. Morphological observations by SEM-EDS showed that the heat treatment affected directly microstructural properties of the alloy. Microstructure of the heat treated samples is composed of intermetallic Ni-rich Ni8Ta and Ta-rich NiTa2 compound in the Ni3Ta matrix. In addition to these phases, orthorhombic Ni3Ta phase was only observed in the sample heat-treated at 1000oC. Structural investigations of alloy the samples by XRD indicated that the martensitic crystal orientation of the samples changed with heat treatments. DSC measurements revealed that all the samples displayed high temperature shape memory behavior with martensitic transformation temperatures of above 200oC. Vicker’s microhardness measurements showed that the microhardness of the alloy influenced dramatically by applying heat treatments, especially at 800 and 900oC. © 2020, Adiyaman University. All rights reserved.
Isıl İşlem Uygulanmış Ni-25,5 at. %Ta Yüksek Sıcaklık Şekil Hatırlamalı Alaşımlarındaki Yapısal Özelliklerin ve Martensitik Faz Dönüşümlerinin İncelenmesi
Keywords: Heat treatment; Martensite; Ni3Ta